Separation of Mo, Cu, Zn and Pb from Concentrates of Fluorite Ore Containing Molybdenum - ZIYADANOGULLARI, RECEP; AKGUN, ABUZER; TEGIN, IBRAHIM; GUZEL, REMZIYE (Asian Journal of Chemistry, 2010)
This study deals with the separation of Mo, Cu, Zn and Pb from concentrates of a flotation process of Elazig region fluorite ore containing of molybdenum. The original ore contained (%) 1.08 Mo, 0.05 Cu, 1.12 Zn, 1.20 Pb and 12 F. The ore concentrate after flotation contained (%) 19.46 Mo, 0.87 Cu, 4.54 Zn and 2.65 Pb. The fluorite itself was separated and left in the residue during flotation process. A hydrometallurgical concentration process was used for the separation of Mo, Cu, Zn and Pb. In view of the existence of sulfide, the concentrate was roasted at 600ºC and the concentrations of dissolved ions were investigated. The result was not fruitful. In the following work, the concentrates were roasted at various temperatures and durations and the samples were later treated in a autoclave at 225ºC with 15 M H2SO4. Under suitable set of conditions Mo, Cu and Zn were dissolved and Pb was left behind in the form of PbSO4. The molybdenum in the solution was separated from copper and zinc by an extraction process by using alamine 336 (trioctylamine). (NH4)2S was used to separate molybdenum from the organic phase. Due to the presence of the other ions such as vanadium, tantalum and niobium, the separation of molybdenum could not be achieved with H2S, but (NH4)2S was utilized in the process.